Cultural Approach Analysis Of Indonesian Children’s Literature Anthology Translation - Christopher Calvin; Ikha Adhi Wijaya (Master Program in Linguistics, Diponegoro University, 2026)
Translating cultural reference means translating Indonesian culture. As a translator for children’s literature, a proper English translation has to be enjoyable, natural, and acceptable both culturally and linguistically. The Agency for Language Development and Cultivation solves the problem of cultural references by applying translation techniques. This research aims at finding out the cultural references translation in “An Anthology of Indonesian Children’s Stories”. This research is qualitative in nature. Not only are there eight translation techniques found, but there are also six cultural references to highlight, namely Ecology, Public life, Social life, Personal life, Customs and Pursuits, Private passions. The research provides another perspective of how to deal with cultural item references in translating Indonesian short stories into English. In An Anthology of Indonesian Children’s Stories’ case, the translators act as a bridge connecting cultural gap between Indonesian and English. Hence, the translation of Indonesian context in English translation is fairly readable.